SISTEM BUDAYA, SOSIAL, KEPRIBADIAN, PERILAKU, DAN HUBUNGAN SIBERNETIK DALAM CERPEN “JUST LIKE A YOUNG GIRL SHOULD” KARYA CHRISTINA KONING - Hadiyanto Hadiyanto; Oktiva Herry Chandra (Endogami: Jurnal Ilmiah Kajian Antropologi, 2022)
This research paper discusses cultural, social, personality, behavioral system and cybernetics relationship in Christina Koning’s Just Like A Young Girl Should. The focus of this research covers the analysis of cultural system encompassing constitution symbol, cognition symbol, evaluation symbol, and expression symbol, social system covering status and role of people in society, personality system including race identity, id, ego, and super ego, behavioral system referring to tendency of society behaviors, and cybernetics relationship reflected in the short story. The comprehensive approach used in this research is eclectic approach by combining more than one research approach to analyze the related phenomena in the short story which is endorsed with Talcott Parsons’s Action Theory. The result of this research indicates that cultural, social, personality, behavioral system, and cybernetics relationship are reflected in teenagers’ life of the main characters in the short story, Kitty and Alain.